La colonialità del potere nei mezzi di comunicazione colombiani. Il caso dello sbiancamento nei telegiornali di RCN - Tenorio, José Manuel Romero; Riccardi, Davide; Jiménez, Adriano Díez (Comparative Cultural Studies: European and Latin American Perspectives, 2019)
This article shows how the coloniality of power manifests itself through the Colombian media, replicating aesthetic whitening paradigms that penetrate into the deepest meanders of cultural representations of ethnic groups, mainly African descendants and indigenous. Through the critical analysis of discourse, applied to the newscasts of the RCN television chain, we observe subtle mechanisms in which power feeds on metaphorical systems that try to neutralize every cultural element in potential conflict with the Eurocentric hegemonic paradigms. In this study, we highlight how reality takes shape through an ad-hoc narrative designed to give an ideologically modern image of the country with a series of stereotyped social representations of cultural diversity. The article concludes by opening a question on how and to what extent the ethnic groups themselves are partly complicit in this system, legitimizing the very structure of power and its own hegemonic narrative.